Land access, livelihood diversification and migration of rural youth in sri lanka - Samaraweera, W.G.R.L.; Dharmadasa, R.A.P.I.S.; Weerahewa, J.; Kumara, P.H.T.; Fernando, P.M.M. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
Selecting an appropriate livelihood is a critical turning point of any youth’s life. Until recent years, most prominent livelihood among youth who reside in rural sector was agriculture, which was inherited from their family. Rural livelihoods have been diversified due to many factors causing a huge social change, and it has led the rural youth to be migrated. Among the many factors, this study was designed to assess whether, the land access influences the choice of agricultural livelihood among rural youth and it affect the rural youth’s choice of migration. A national representative sample of rural youth were isolated from the Household Income and Expenditure Survey (2016) data, compiled by Department of Census and Statistics. A multinomial logit model under random utility framework was used to assess the livelihood diversification: the choice of rural youths’ livelihood among mutually exclusive alternatives. A probit model of migration outcome was employed to assess the rural youth’s choice of migration with regards to land access. The multinomial logit model revealed that land access is strongly associated with the agricultural livelihood choice and urban salaried employment choice of rural youth. Being a female youth makes the choice of livelihood less likely to be agriculture in contrast to male youth. Education level of youth act as an upward driver in choosing urban salaried employment while youth tend not to choose agriculture as a livelihood opportunity with their education. Probit model of migration revealed that tendency to migrate reduces with land accessibility. Therefore, land access is a crucial factor for rural youth to choose agricultural livelihoods. Land access is also a crucial factor for rural youth not to be migrated. Thus, the policies required to be reformed to increase the land access to rural youth in Sri Lanka to address the adverse effects of this social change.
Keywords: Employment Choice of Rural Youth; Farmland availability; Non- farm Employment; Sustainable Agriculture